Prognozowanie szeregów czasowych z nieregularnymi wahaniami okresowymi metodą najmniejszego sympleksu - Szanduła, Jacek (Forecasting Time Series with Irregular Periodic Fluctuations by the Method of the Smallest Simplex, 2006)
The paper presents the conception of using the Sugihara and May's method of the smallest simplex for forecasting time series with irregular periodic fluctuations . The idea of the method has been summarized. The method has been tested on generated time series: a) with constant cycle length and random amplitude,b) with constant amplitude and random cycle length,c) with random both amplitude and cycle length.The forecasts have been verified. The results of the method have been compared with ARIMA models.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 112-122